Klasyfikacja rozkładów dochodów gospodarstw domowych - Łukasiewicz, Piotr; Koszela, Grzegorz; Orłowski, Arkadiusz (Households Classification of Income Distributions, 2008)
An income distributions classification of Polish households from 16 provinces of Poland is presented. The research material was gained from microobservations issued from households incomes examined by GUS. Empiric income distributions were approximated using Dagum model with three parameters. It enables to identify each of 16 income distributions with certain point in three dimensional space. Objects obtained this way were put under classification using different clustering methods. By the examination of differentiation inside the group and between groups, the best income distributions division was selected.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 535-543